Essential oil of Thymus vulgaris on the sanitary and physiological quality of seeds of Caesalpinia ferrea - Feitosa da Silva, Diana; Vargas Borges, Elizene; Ribeiro Coutinho, Pablo Wenderson (Scientia Agraria Paranaensis, 2021)
As for most plant species occurring in forests, Caesalpinia ferrea Mart. Ex Tul. has been presenting some phytosanitary problems, and thus research efforts have been increased considering the use of alternative treatments using as basis essential oils like Thymus vulgaris L., which is responsible for antimicrobial activity. The objective of this study was to evaluate the influence of the essential oil from thyme on the sanitary and physiological quality of ironwood seeds. The experiment was carried out in a completely randomized design with four repetitions with 50 seeds. The treatments considered the use of the thyme essential oil at concentrations of 0, 2, 4, 6, 8, and 10%. The ironwood seeds were obtained from matrices taken at random, moved to the laboratory, where sanitary evaluations were carried out using the Blotter test method in 25±2°C temperature and in a 12h photoperiod. After 7 days, with the aid of a microscope, fungi were identified. Next, physiological analysis were conducted — germination, first count of germination, and germination speed index. Measurements of the shoot and root parts of the seedlings, shoot dry matter, and root dry matter were taken. According to the obtained results in this work, it was verified that the T. vulgaris dry matter in all concentrations presented different results, noting that when the oil concentration increases, the occurrence of pathogens decreases, which proves that the T. vulgaris essential oil has specific action on some genera of fungi.